2010
DOI: 10.1007/s10551-010-0552-8
|View full text |Cite
|
Sign up to set email alerts
|

Suspicion and Perceptions of Price Fairness in Times of Crisis

Abstract: suspicion, price fairness, price gouging, crisis, affect,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…In addition, by voicing their doubts to friends and acquaintances, consumers can vent their frustration and attain retribution for their dissatisfaction (Chan and Wan, 2008). Thus, in the presence of green skepticism, consumers are likely to pose their questions, communicate their doubts, share their qualms, and warn others about green products (Ferguson et al, 2011), portraying them in an overall negative light to friends and acquaintances.…”
Section: Outcomes Of Green Skepticismmentioning
confidence: 99%
“…In addition, by voicing their doubts to friends and acquaintances, consumers can vent their frustration and attain retribution for their dissatisfaction (Chan and Wan, 2008). Thus, in the presence of green skepticism, consumers are likely to pose their questions, communicate their doubts, share their qualms, and warn others about green products (Ferguson et al, 2011), portraying them in an overall negative light to friends and acquaintances.…”
Section: Outcomes Of Green Skepticismmentioning
confidence: 99%
“…In fact, Campbell (1999) found that providing no reason can lead to negative inferences and subsequent perceptions of price unfairness. Additionally, if there are peripheral cues such as plausible negative motives for a price increase, consumers may become suspicious, which can result in increased perceived price unfairness (Ferguson et al, 2011). Bearden et al (2003) found that providing the seller's costs (i.e.…”
Section: Extent Of Information Disclosedmentioning
confidence: 99%
“…Perhaps, our extended emotional value indicator which incorporates a greater relational dimension is a factor at play in the different results. It may also indicate that emotional value, which is more relationally superficial, holds less value for consumers in a sector requiring deeper relationships based on trust (Ferguson et al, 2011;Birchall, 2013). This may also highlight the need to extend the emotional value indicator to incorporate relational dimensions, particularly in high contact services (O'Malley et al, 2008) such as banking.…”
mentioning
confidence: 99%